Transformational Leadership in Improving Lecturer Performance in Higher Education - Yanti Hasbian Setiawati; Deti Rostini; Iim Wasliman; Hanafiah (Yayasan Azka Hafidz Maulana, 2022)
This research is motivated by the low performance of lecturers, both in the fields of teaching, research and community service in universities. The general objective of this research is to examine transformational leadership in improving the performance of lecturers in higher education. Meanwhile, the specific objective is to identify and analyze transformational leadership in improving the performance of lecturers in higher education through 1) Individualized Consideration. 2) Intellectual Stimulation. 3) Inspirational Motivation. 4) Idealized Influence. 5) Factors inhibiting lecturer performance. 6) Solutions to overcome obstacles. and 7) lecturers' performance in higher education. This research is based on transformational leadership theory from Bernard M Bass and performance theory from Michael Armstrong. This research uses a qualitative approach with descriptive methods and research techniques of observation, interviews and documentation. The results showed that the leaders at the two universities studied had implemented transformational leadership through; 1) individualized consideration by giving tolerance, being fair, empowering subordinates, being democratic, participatory and giving awards. 2) Intellectual Stimulation by innovating, being professional, conducting self-evaluation, leading with a collegial collective system and high creativity. 3) Inspirational Motivation by conducting effective communication, providing motivation and being an inspiration for subordinates. 4) Idealized Influence by being a role model for subordinates, being honest, authoritative, having high spirits, giving reasonable compliments and being able to accept differences of opinion while still using lively facial expressions. 5) Identification of factors inhibiting lecturer performance including a) low competence of lecturers, b) inadequate tridharma facilities and infrastructure and c) tridharma budget that has not been optimal. 6) Solutions in dealing with obstacles that occur through a) holding seminars, workshops and training activities, b) improving tridharma facilities and infrastructure, and c) preparing periodic annual budget plans. 7) Lecturer performance after the implementation of transformational leadership in higher education, education sector is 90%, research field is 82% and community service is 84%.